(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
the contrary, e-security of funds with the help of passwords, PIN, TIN, OTP, firewall system, traces and detection of unauthorized transaction are other important aspects of digital banking under regulatory provisions. Some other forms of electronic transactions are also popular in India that are not included in legal Bankers, intermediaries and investors are adapting quality banking practices and opting for latest advancements in banking technology for offering better banking solutions. Digital banking is one of the paramount booms in the last 15 years for the Indian economy. Indian banking sector is undergoing plethora of reforms including legal, financial, technological and economic reforms. With the advent of World Wide Web, Web 3.0, fifth generation devices, legal framework for dealing with technology, electronic governance, vigilance and constant innovation in the field of information technology our lives have become so complicated as never before. Nevertheless, it has also helped to bring electronic insurgency in the global banking and financial transactions. Where banking transactions are carries out in a speedy, smooth, transparent, paperless, authentic and reliable manner. Digital banking is a wider term covering all the technical terminology and ICT tools i.e., e-banking, internet banking, m banking, SMS banking, app banking etc. Moreover, our heavy dependency on electronic gadgets, mobiles and digital tools to electronic commence business and routine transactions is also increasing day by day. Unfortunately, at the same time we are exposed to many closed and open networks where the reliability and safety is a challenge for regulatory authority. The growing trends of cyber frauds including off line and online financial activities are affecting a large number of population. Financial frauds with online payments, Mobile banking, ATM machines, Mobiles data, Electronic cards and net banking transactions are some challenges faced by banking concerns and IT Experts where IT department is not core area for banking concern. Most of the IT operations are outsourced including the security, plastic money, website maintenance, printing of debit/credit cards, collection etc. Lupus and other security developers are worried about security system, virus attacks, app safety for androids and vault safety.